2-Hydroxy-4-methoxybenzaldehyde, a more effective antifungal aroma than vanillin and its derivatives against Fusarium graminearum, destroys cell membranes, inhibits DON biosynthesis, and performs a promising antifungal effect on wheat grains - Li, Qian; Wang, Chong; Xiao, Hongying; Zhang, Yiming; Xie, Yanli (Frontiers in Microbiology, 2024)
Fusarium graminearum (F. graminearum) is a severe pathogen threatening the safety of agriculture and food. This study aimed to explore the antifungal efficacies of several plant-derived natural compounds (vanillin and its derivatives) against the growth of F. graminearum and investigate the antifungal mechanism of 2-hydroxy-4methoxybenzaldehyde (HMB), the strongest one. The minimum inhibitory concentration (MIC) of HMB in inhibiting mycelial growth was 200 g/mL. HMB at MIC damaged cell membranes by increasing the permeability by about 6-fold (P  0.05) as evidenced by propidium iodide (PI) staining. Meanwhile, the content of malondialdehyde (MDA) and glycerol was increased by 45.91% and 576.19% by HMB treatment at MIC, respectively, indicating that lipid oxidation and osmotic stress occurred in the cell membrane. Furthermore, HMB exerted a strong antitoxigenic role as the content of deoxynivalenol (DON) was remarkably reduced by 93.59% at MIC on 7 th day. At last, the antifungal effect of HMB against F. graminearum was also confirmed on wheat grains. These results not only revealed the antifungal mechanism of HMB but also suggested that HMB could be applied as a promising antifungal agent in the preservation of agricultural products.